Differentiation of Epileptic Brain Abnormalities among Neurological Patients at Taif Region Using MRI - Nahla L. Faizo; Amani A. Alrehaili (International Journal of Clinical Practice, 2023)
This study was conducted to assess the prevalence of epilepsy among different age groups and gender of neurological patients in the Taif region and define the most common brain lesion, affecting epileptic patients living in the Taif city using MRI. Data from 150 patients who were clinically diagnosed with epilepsy and had brain MRIs were analyzed using SPSS. Statistical significance was considered when the p value is 0.05. The percentage of epilepsy was generally higher in males than in females in the Taif city, and seizures were different between the studied age groups. However, epilepsy was more pronounced in females than in males at certain age groups. Moreover, white matter lesions were most commonly found in the studied group (27.7%), followed by focal lesions, edema, and stroke with equal percentages (16.9%) and less commonly with congenital diseases (12%) and atrophic changes (9.6%). Epilepsy was more pronounced in females than in males at certain age groups. White matter lesions were identified as the most common lesion, presenting in epilepsy patients in the Taif city.